2013
DOI: 10.1007/s10103-013-1486-z
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting diode phototherapy improves muscle recovery after a damaging exercise

Abstract: The goal of the present study was to determine the effect of light-emitting diode phototherapy (LEDT) at 630 nm on muscle recovery after a damaging eccentric exercise bout. Seventeen healthy young male volunteers, without previous experience with eccentric exercise, were included in a randomized double-blinded placebo-controlled trial. They were divided into a LEDT (n = 8) and a PLACEBO group (n = 9). To induce muscle damage, subjects performed 30 eccentric contractions with a load of 100 % of maximal voluntar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
0
28
0
3
Order By: Relevance
“…Investigating the effects of PBM by LEDT (630 nm) applied after an exercise protocol to induce muscle damage by eccentric elbow flexion/extension, Borges, Cerqueira (level 1b) reported a reduction in DOMS, and a slower decay in the isometric force able to be exerted by the LEDT group when compared to the placebo group in a randomized, double‐blind, placebo‐controlled trial. The authors also reported less restriction or a smaller decrease in the range of motion possible in the LEDT group 24 h, 48 h, 72 h and 96 h after induction of muscle damage.…”
Section: Resultsmentioning
confidence: 99%
“…Investigating the effects of PBM by LEDT (630 nm) applied after an exercise protocol to induce muscle damage by eccentric elbow flexion/extension, Borges, Cerqueira (level 1b) reported a reduction in DOMS, and a slower decay in the isometric force able to be exerted by the LEDT group when compared to the placebo group in a randomized, double‐blind, placebo‐controlled trial. The authors also reported less restriction or a smaller decrease in the range of motion possible in the LEDT group 24 h, 48 h, 72 h and 96 h after induction of muscle damage.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects seen in recent studies were obtained with red 8,9 and infrared wavelengths 9-13 generated by both laser [8][9][10][11][12][13][14] and LED [14][15][16][17] devices. Various exercises that represent sport-specific activities have been tested: repeated contractions, 8,10,11,13,15 isometric sustained contraction, 9,16,17 cycling, 14 and running. 12 Only a few investigators have compared PBM with other physical agents 18,19 and addressed the effectiveness of laser versus LEDs.…”
mentioning
confidence: 99%
“…Thus, it is plausible that the use of bioceramic clothes in our study improved muscle soreness in periods when this variable was not being monitored. On the other hand, Borges et al 40 applied 630 nm LED on the biceps muscle after eccentric exercise bouts and observed that this intervention was sufficient to significantly relieve muscle soreness up to 96 h after LED application. However, the authors emphasize phototherapy was applied to an injured muscle, which might cause different effects than application before potentially effects different from 40 .…”
Section: Discussionmentioning
confidence: 99%